FAKTOR–FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENGELOLAAN SEDEKAH PADA YAYASAN SEDEKAH NGIDER INDONESIA - Surya Agustina; Trian Zulhadi; Mawardi Mawardi (Jurnal Cakrawala Ilmiah, 2023)
This research aims to analyze what factors influence the effectiveness of alms management at the Ngider Indonesia Alms Foundation in Ciracas District, East Jakarta using quantitative methods with primary data sources obtained from distributing questionnaires via the Google Form digital platform which was processed with the help of the SmartPLS 3.0 program . Effectiveness can be measured from several indicators such as goal achievement, adaptation, integration and one other indicator outside the effectiveness measurement indicator, namely leadership. The type of research used was field research (Field Research) with a sample of 400 people using cluster random sampling technique. The research results concluded that partially the leadership, goal achievement and adaptation variables had a significant effect on the effectiveness of alms management, while the integration variable had no effect on the effectiveness of alms management. The variable that dominates the effectiveness of alms management is the leadership variable. Simultaneously, the variables of leadership, goal achievement, integration and adaptation are able to influence the effectiveness of alms management at the Ngider Indonesia Alms Foundation in Ciracas District, East Jakarta by 54.1%, while the remaining 45.9% is influenced by other variables not examined in this research.